Optimal Fiscal Substitutes For The Exchange Rate In A Monetary Union - Christoph Kaufmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies Ramsey-optimal monetary and fiscal policy in a New Keynesian 2-country open economy framework, which is used to assess how far fiscal policy can substitute for the role of nominal exchange rates within a monetary union. Giving up exchange rate flexibility can result in high welfare costs, which depend significantly on whether firms set prices in producer or in local currency. By using only one tax instrument per country and robust to changes in the calibration, the welfare costs can be reduced by 86% in case of producer currency pricing and by 68% in case of local currency pricing. Optimal policy in a monetary union can be described as a fiscal devaluation: if a nominal devaluation of the domestic currency is optimal under flexible exchange rates, optimal fiscal policy in a monetary union is a relative increase of the domestic VAT.
Keywords: F41; F45; E63; 330